The Role of Green Human Resource Management Implementation on Innovative Work Behaviour at Wijaya Kusuma University Surabaya - Darmanto (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
This study aims to analyze the influence of green hiring, green training, and green compensation, as well as the mediating role of green performance management system on innovative work behaviour of education personnel and educators at Wijaya Kusuma University, Surabaya (UWKS). This study is a causal study with a quantitative approach. Data collection using questionnaires distributed to 225 education personnel and educators, which were then analyzed using SEM PLS. The results of the study prove that green hiring, green training, and green compensation have a significant positive effect on the innovative work behaviour of educational staff and educators at UWKS. green performance management system also has a mediating role in the influence of green hiring, green training, and green compensation on innovative work behaviour.